Impact of water temperature and structural parameters on the hydraulic labyrinth-channel emitter performance - Ahmed I. Al-Amoud; Mohamed A. Mattar; Mohamed I. Ateia (Spanish Journal of Agricultural Research, 2014)
The effects of water temperature and structural parameters of a labyrinth emitter on drip irrigation hydraulic performance were investigated. The inside structural parameters of the trapezoidal labyrinth emitter include path width (W) and length (L), trapezoidal unit numbers (N), height (H), and spacing (S). Laboratory experiments were conducted using five different types of labyrinth-channel emitters (three non-pressure compensating and two pressure-compensating emitters) commonly used for subsurface drip irrigation systems. The water temperature effect on the hydraulic characteristics at various operating pressures was recorded and a comparison was made to identify the most effective structural parameter on emitter performance. The pressure compensating emitter flow exponent (x) average was 0.014, while non-pressure compensating emitter’s values average was 0.456, indicating that the sensitivity of non-pressure compensating emitters to pressure variation is an obvious characteristic (p<0.001) of this type of emitters. The effects of water temperature on emitter flow rate were insignificant (p>0.05) at various operating pressures, where the flow rate index values for emitters were around one. The effects of water temperature on manufacturer’s coefficient of variation (CV) values for all emitters were insignificant (p>0.05). The CV values of the non-pressure compensating emitters were lower than those of pressure compensating emitters. This is typical for most compensating models because they are manufactured with more elements than non-compensating emitters are. The results of regression analysis indicate that N and H are the essential factors (p<0.001) to affect the hydraulic performance.